Knowledge and Preventive Practices About Osteoporosis Among Elementary School Teachers of Bandar-Abbas in 2020 - Nikoobar, Ali; Kolahi, Ali-Asghar (Frontiers in Nutrition, 2022)
Purpose: To assess knowledge and ‎preventive practices about osteoporosis among ‎elementary school teachers of ‎Bandar-Abbas in 2020 Materials and Methods: In this cross-sectional study, ‎the schools were ‎selected using simple random sampling, ‎and the teachers were invited to fill in an ‎online ‎questionnaire. The knowledge section of the ‎questionnaire assessed general ‎knowledge and ‎knowledge regarding ‎risk/protective factors, nutrition, and ‎physical activity. The preventive ‎practices section ‎assessed dietary habits using a food frequency ‎questionnaire, asking about 16 ‎items ‎in six groups, intakes of which were compared to the recommendations of the Iranian Food ‎Pyramid. This section also assessed physical activity using the ‎International Physical Activity ‎Questionnaire.‎ Results: Totally, 377 teachers ‎with a mean (standard deviation [SD]) age of ‎38 (6.7) participated in this study. The ‎‎level of overall knowledge of ‎‎128 (34%) teachers was high, ‎222 (58.9%) moderate, ‎‎and ‎‎27 (7.2%) ‎low. The ‎median (interquartile range [IQR]) intakes of ‎fruits (‎2 [1‎–‎2]) and meats/‎‎eggs (1.7 [1.4‎–‎2.2]) were ‎adequate, while ‎those of dairy ‎‎products (‎1.5 [0.9‎–‎2.3]), nuts/‎legumes (‎0.5 [0.2‎–‎‎‎1.1]), and ‎vegetables (‎0.3 [1.1‎–‎1]) were ‎inadequate. The median ‎‎(IQR) ‎intakes of ‎tea/‎coffee (1 [0.6‎–‎2]) and cola‎‎‎‏) ‏‎‎0.1 [0‎–‎0.3]) were ‎considered ‎limited. The physical ‎activity level of 121 (32.1%) teachers was high, 124 (32.9%) ‎moderate, ‎and ‎‎‎135 (35%) low.‎ Conclusion: Knowledge of the teachers about osteoporosis was ‎moderate, and their ‎preventive practices ‎were ‎somewhat adequate concerning dietary habits and ‎‎moderate concerning physical activity.‎